Religiosity/Spirituality and Mental Health in Older Adults: A Systematic Review and Meta-Analysis of Observational Studies - Coelho-Júnior, Hélio José; Calvani, Riccardo; Panza, Francesco; Allegri, Riccardo F.; Picca, Anna; Marzetti, Emanuele; Alves, Vicente Paulo (Frontiers in Medicine, 2022)
Objectives: The present study investigated the association between religious and spiritual (RS) practices with the prevalence, severity, and incidence of mental health problems in older adults. Methods: We conducted a systematic review and meta-analysis of cross-sectional and longitudinal studies that investigated older adults aged 60+ years and assessed RS using valid scales and questions from valid scales, and mental health according to validated multidimensional or specific instruments. Studies were retrieved from MEDLINE, LILACS, SCOPUS, CINAHL, and AgeLine databases until July 31, 2021. The risk of bias was evaluated using the Newcastle - Ottawa Quality Assessment Scale (NOS). A pooled effect size was calculated based on the log odds ratio (OR) and Z-scores. This study is registered on PROSPERO. Results: One hundred two studies that investigated 79.918 community-dwellers, hospitalized, and institutionalized older adults were included. Results indicated that high RS was negatively associated with anxiety and depressive symptoms, while a positive association was observed with life satisfaction, meaning in life, social relations, and psychological well-being. Specifically, people with high spirituality, intrinsic religiosity, and religious affiliation had a lower prevalence of depressive symptoms. In relation to longitudinal analysis, most studies supported that high RS levels were associated with a lower incidence of depressive symptoms and fear of death, as well as better mental health status. Conclusion: Findings of the present study suggest that RS are significantly associated with mental health in older adults. People with high RS levels had a lower prevalence of anxiety and depressive symptoms, as well as reported greater life satisfaction and psychological well-being, better social relations, and more definite meaning in life. Data provided by an increasing number of longitudinal studies have supported most of these findings.